Polarization of Narrowband VLF Transmitter Signals as an Ionospheric Diagnostic. Issue 1 (26th January 2018) - Gross, N. C.; Cohen, M. B.; Said, R. K.; Gołkowski, M.
Abstract: Very low frequency (VLF, 3–30 kHz) transmitter remote sensing has long been used as a simple yet useful diagnostic for the D region ionosphere (60–90 km). All it requires is a VLF radio receiver that records the amplitude and/or phase of a beacon signal as a function of time. During both ambient and disturbed conditions, the received signal can be compared to predictions from a theoretical model to infer ionospheric waveguide properties like electron density. Amplitude and phase have in most cases been analyzed each as individual data streams, often only the amplitude is used. Scattered field formulation combines amplitude and phase effectively, but does not address how to combine two magnetic field components. We present polarization ellipse analysis of VLF transmitter signals using two horizontal components of the magnetic field. The shape of the polarization ellipse is unchanged as the source phase varies, which circumvents a significant problem where VLF transmitters have an unknown source phase. A synchronized two‐channel MSK demodulation algorithm is introduced to mitigate 90° ambiguity in the phase difference between the horizontal magnetic field components. Additionally, the synchronized demodulation improves phase measurements during low‐SNR conditions. Using the polarization ellipse formulation, we take a new look at diurnal VLF transmitter variations, ambient conditions, and ionospheric disturbances from solar flares, lightning‐ionospheric heating, and lightning‐induced electron precipitation, and find differing signatures in the polarization ellipse. Key Points: Polarization ellipse analysis combines two horizontal magnetic field phasors and is used to remote sense the lower ionosphere Synchronized MSK demodulation enables polarization ellipse analysis and improves performance in low‐SNR conditions We observe the day/night terminator, early/fast event, LEP event, and a solar flare, and find variable polarization signatures